1D sediment transport modelling in Langat river by using quasi unsteady hecras - Khair, Badri (2014)
The main purpose of this study is to study sediment transport characteristics at Langat River. Langat River is located in the state of Selangor and it is subjected to regular flooding. Sediment transport capabilities can be known by using Hydraulic Engineering Center's River Analysis System program (HEC-RAS). The appropriate data required to create the model. The data needed to use in HEC-RAS is cross sectional data and elevation data. HEC-RAS can create the sediment transport and hydraulic models. The sediment transport model will calculates sediment transport capacity with a number of available methodologies. In this research, HEC-RAS can show sediment transport. The HEC-RAS model can calibrate and gives the values of Manning's coefficients of roughness for the Langat River. HEC-RAS also can predict the changes of bed elevation. The model will conclude that there is a significant increase in river bed depth due to development, which means there is no change in flooding behaviour was detected in the short term. This paper will be focused only on bed load sediment. The result of 6 years stream flow shows there are some area had faced sediment transport and erosion of the river. By using the England Hansen function in HEC RAS had shown a little change in the river. From the simulation, the result shows the section that experienced sediment transport at station 943 (1.45km from the upstream part at Bangi) and station 959 (1.05km from the upstream part at Bangi), and station 972 (725rn from the upstream part at Bangi) that experienced the erosion of river.